Before or After: Evolving Neoadjuvant Approaches to Locally Advanced Non-Small Cell Lung Cancer - Lewis, Jennifer; Gillaspie, Erin A.; Osmundson, Evan C.; Horn, Leora (Frontiers in Oncology, 2018)
The treatment of patients with stage IIIA (N2) non-small cell lung cancer (NSCLC) is one of the most challenging and controversial areas of thoracic oncology. This heterogeneous group is characterized by varying tumor size and location, the potential for involvement of surrounding structures, and ipsilateral mediastinal lymph node spread. Neoadjuvant chemotherapy, administered prior to definitive local therapy, has been found to improve survival in patients with stage IIIA (N2) NSCLC. Concurrent chemoradiation has also been evaluated in phase III studies in efforts to improve control of locoregional disease. In certain instances, a tri-modality approach involving concurrent chemoradiation followed by surgery, may offer patients the best chance for cure. In this article, we provide an overview of the trials evaluating neoadjuvant therapy in patients with stage IIIA (N2) NSCLC that have resulted in current practice strategies, and we highlight the areas of uncertainty in the management of this challenging disease. We also review the current on-going research and future directions in the management of stage IIIA (N2) NSCLC.